1997
DOI: 10.1099/00221287-143-5-1521
|View full text |Cite
|
Sign up to set email alerts
|

FNR-dependent repression of ndh gene expression requires two upstream FNR-binding sites

Abstract: The ndh gene of Escherichia coli encodes a non-proton-translocating NADH dehydrogenase (Ndhll) that is anaerobically repressed by the global transcription regulator, FNR. FNR binds at two sites (centred at -505 and University of Sheff ield,-Firth Court, Western Bank, Sheffield 510 ZTN, UK -94.5) in the ndh promoter but the mechanism of FNR-mediated repression appears not to be due to promoter occlusion. This mechanism has been investigated using an aerobically active derivative of FNR, FNR* (FNR-D154A), with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 37 publications
(72 reference statements)
2
47
0
Order By: Relevance
“…Thus, in an appropriate context FNR can activate transcription when positioned at ¹41 (FFpmelR ), and additional upstream FNR sites can produce inhibitory ( yfiD þ FNR), neutral/positive ( yfiD þ FNR variants or HlyX) or activating (FF-FFansB þ FNR) interactions. The potential for switching between activation and repression of transcription merely by altering the position of an upstream FNR site suggests that FNR repressible promoters, such as that of the ndh gene (Meng et al, 1997), may have evolved through duplication and shuffling of the positions of FNR sites. By this mechanism, promoter regions that display the full range of FNR regulation, from synergistic activation to full repression, could be generated.…”
Section: The Role Of Fnr II In the Control Of Yfid Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in an appropriate context FNR can activate transcription when positioned at ¹41 (FFpmelR ), and additional upstream FNR sites can produce inhibitory ( yfiD þ FNR), neutral/positive ( yfiD þ FNR variants or HlyX) or activating (FF-FFansB þ FNR) interactions. The potential for switching between activation and repression of transcription merely by altering the position of an upstream FNR site suggests that FNR repressible promoters, such as that of the ndh gene (Meng et al, 1997), may have evolved through duplication and shuffling of the positions of FNR sites. By this mechanism, promoter regions that display the full range of FNR regulation, from synergistic activation to full repression, could be generated.…”
Section: The Role Of Fnr II In the Control Of Yfid Expressionmentioning
confidence: 99%
“…In conclusion, the yfiD promoter joins the ndh (Meng et al, 1997) and fdnGHI (Guest et al, 1996) promoters as an FNR-regulated promoter with an inhibitory upstream FNR site. The inhibitory action of FNR bound at the most upstream site appears to be mediated through proteinprotein contacts involving the face of FNR that includes AR1.…”
Section: The Role Of Fnr II In the Control Of Yfid Expressionmentioning
confidence: 99%
“…Measurement of the relative amounts of an FNR-activated transcript (dmsA; Lamberg & Kiley, 2000) and an FNR-repressed transcript (ndh; Green & Guest, 1994;Meng et al, 1997;Spiro et al, 1989) in anaerobic cultures of MG1655 and MG1655 clpX revealed that the dmsA transcript was~2?5-fold more abundant, and the ndh transcript was~1?5-fold less abundant in the clpX mutant (Fig. 2b).…”
Section: Stability Of the E Coli Fnr Protein In Vivomentioning
confidence: 99%
“…The [4Fe-4S] form of FNR acts as both a positive and a negative regulator of gene expression, activating transcription by recruiting RNA polymerase, or repressing transcription by inhibiting the formation of productive promoter-RNA polymerase interactions (Barnard et al, 2004;Bell & Busby, 1994;Blake et al, 2003;Browning et al, 2003;Green & Marshall, 1999;Green et al, 1998;Lamberg & Kiley, 2000;Lamberg et al, 2002;Li et al, 1998; Lonetto et al, 1998;Marshall et al, 2001;Meng et al, 1997;Williams et al, 1997;Wing et al, 2000). Exposure of E. coli to air is sensed by the , 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation